2021
DOI: 10.1002/pat.5232
|View full text |Cite
|
Sign up to set email alerts
|

Copolymerization of nadic anhydride with styrene: Reactivity ratios

Abstract: The free radical copolymerization of nadic anhydride (NA) and styrene (St) at 80°C has been investigated for the first time. The copolymerization was done in toluene using benzoyl peroxide as initiator. The monomer reactivity ratios were calculated from the copolymer composition (estimated from the acid value) by using Fineman–Ross, Kelen–Tüdös, and Extended Kelen–Tüdös methods. The reactivity ratios (rNA, = 0.34, rST = 0.84) implied a good copolymerizability for the monomer pair and existence of an azeotropic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Based on previous studies, the reactivity ratios were estimated using Fineman–Ross, Inverted Fineman–Ross, and Kelen–Tüdös methods. The mole fraction in the feed ( f ) and the mole fraction in the copolymer determined by 1 H NMR ( F ) are shown in Table S6 (Supporting Information). The results showed that the r 1 × r 2 , r 1 × r 3 , and r 1 × r 4 of AAOK were close to 1, and the r 1 , r 2 , r 3 , and r 4 were all <1 (Table S7, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous studies, the reactivity ratios were estimated using Fineman–Ross, Inverted Fineman–Ross, and Kelen–Tüdös methods. The mole fraction in the feed ( f ) and the mole fraction in the copolymer determined by 1 H NMR ( F ) are shown in Table S6 (Supporting Information). The results showed that the r 1 × r 2 , r 1 × r 3 , and r 1 × r 4 of AAOK were close to 1, and the r 1 , r 2 , r 3 , and r 4 were all <1 (Table S7, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The copolymer reactivity ratio of KH-570 with each monomer was estimated by the Fineman–Ross, inverted Fineman–Ross, and Kelen–Tüdös methods. A series of copolymers were synthesized as the ratios of AAOK-1, AAOK-2, AAOK-3, and AAOK-4, and the reaction time of the copolymer were controlled at 10 min to maintain low conversations (<30%). The mole fraction of KH-570 in the copolymers was determined from the integration ratios of the corresponding peaks as determined by 1 H NMR.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, in this case, it was separately determined for the nadic anhydride-styrene pair (Table 3). [27] The reactivity ratio implies that nadic groups have only a moderate propensity for copolymerization. Homo or co-polymerization of these groups normally proceeds with great difficulty due to the isolated nature of the double bond and the presence of allylic proton that led to degenerative transfer.…”
Section: Tensile Flexural Impact and Fracture Propertiesmentioning
confidence: 99%
“…The reactivity ratios of nadic with styrene (r n = 0.34, r s = 0.84) predict reasonably good proportion of adjacent sequence of polyether. [27] This may not be conducive for a tough system as this creates an environment for crystallization of the polyether segments. Too much crystallinity of polyether can result in a brittle matrix.…”
Section: Tensile Flexural Impact and Fracture Propertiesmentioning
confidence: 99%
See 1 more Smart Citation